Development of a Chatbot-Based Assessment System for Evaluating Career Readiness in Vocational Education - Nurwahyuddi Nurwahyuddi; Adi Dewanto (Jurnal Paedagogy, 2026)
This study aims to develop, assess the feasibility of, and evaluate the effectiveness of a web-based chatbot, TemanKarir, for measuring vocational high school students’ career readiness. The research employed a Research and Development (R&D) method using the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The chatbot was developed using the Botpress platform and integrated with Google Sheets, WordPress, the Telegram Bot API, and QuickChart. The assessment instrument was based on the Employability Skills Framework and comprised 75 items across nine skill dimensions. All items demonstrated strong content validity (Aiken’s V = 0.75–1.00), satisfactory item validity (r = 0.339–0.813), and high internal consistency (Cronbach’s α = 0.985). The participants included two content experts, two media experts, and 50 Grade XI vocational high school students. Data were analyzed using descriptive statistical techniques based on a four-point Likert scale and software quality evaluation criteria from the ISO/IEC 25010 standard. The results indicate that: (1) the TemanKarir chatbot was successfully developed with key features, including career readiness assessment, automated feedback, result summaries for guidance counselors, and follow-up guidance recommendations; (2) the chatbot was rated as highly feasible based on evaluations by content experts (mean score = 3.62) and media experts (mean score = 3.52); and (3) the chatbot demonstrated high effectiveness as an assessment tool, with strong scores for effectiveness (3.57), efficiency (3.58), and user satisfaction (3.56). Overall, the findings confirm that the TemanKarir chatbot is both feasible and effective for assessing vocational high school students’ career readiness and contributes positively to their career development processes.